Pengaruh Harga CPO Dunia dan Kurs USD/IDR Terhadap Volume Ekspor CPO Indonesia Perspektif Ekonomi Islam - Salwanisa, Nabila; Iqbal Fasa, Muhammad; Kurniawan, Agus (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This paper analyzes the influence of global CPO prices and the USD/IDR exchange rate on Indonesia’s CPO export volume from 2013 to 2023 within the context of Islamic economics. Employing a quantitative approach, this paper utilizes Ordinary Least Squares (OLS) regression analysis on time series data sourced from BPS, GAPKI, Ditjenbun, Bank Indonesia, and IndexMundi. The results indicate that, partially, global CPO prices and the USD/IDR exchange rate do not have a significant effect on Indonesia’s CPO export volume, as evidenced by p-values greater than 0.05. Simultaneously, the F-test confirms that both variables do not have a significant impact. The coefficient of determination (R2 = 0.2819) suggests that only 28.19% of the variation in export volume can be explained by these two factors, while 71.81% is influenced by other variables not included in the model. From an Islamic economics perspective, justice (al-adl), transparency (as-shafafiyyah), and the prohibition of speculation (gharar and maysir) play crucial roles in ensuring fair trade practices in the CPO industry. This paper emphasizes the need for further research incorporating additional factors such as government policies, global demand, and production levels to develop a more comprehensive model. Furthermore, an in-depth exploration of Islamic trade principles and their application in the CPO sector is recommended to enhance the alignment of the industry with Sharia-compliant trade ethics.